Effect of fluence smoothening in intensity modulated radiotherapy planning and delivery - B. Rekha Reddy; C. Varatharaj; Ravikumar M.; Ganesh K.M. (International Journal of Medical Research and Review, 2018)
Objective: In Intensity Modulated Radiotherapy (IMRT) planning, optimization is a computational problem, potentially susceptible to noise and artifacts (high frequency spatial fluctuations) producing sharp fluence peaks and valleys in millimetric spatial scale. A solution to this problem is to smooth the beam profiles.Methods and Materials: In the Eclipse TPS, fluence smoothing is achieved within the objective function of the inverse treatment planning systems. Plans were developed for a 6 MV photon beam from a Varian Clinac-DHX equipped with a 120 leaves MLC. Total of 160 dose plans were compared and fed into the analysis process. The dose plan quality has been analysed in terms of Statistical computation by means of two-sided paired t-test between two smoothening levels (s25 and s75) in terms of Homogeneity-Index, Conformity-Index, Target dose coverage and OAR dose differences in terms of max, min and mean doses.Results: From our present study on the influence of smoothening of fluence levels in IMRT plans results, there was a reduction in total MU’s with no significant statistical variation in terms of mean differences of HI Index, CI index, PTV coverages, OAR doses. Moreover, the reduction in MU’s will help the less head leakage dose hence the lower whole-body dose, which will help the patient to reduce the chances for secondary malignancies.Conclusion: Hence, we conclude that, higher fluence smoothening levels with acceptable difference in target coverage and minimum variation of OAR should be selected for the execution.